Late Ottoman Perspectives on the South African War (1899-1902): the Work of Ismail Kemal Vlora - Karadağ, Esma (Department of Historical Studies, 2020)
The South African War of 1899−1902 or Anglo-Boer War was one of the modern examples of propaganda in history. It revealed an enormous agitprop conducted by British and Boer forces. The European and American public closely followed the struggle between the mighty British Empire and the “little white Christians”. This thesis examines the pro-British propaganda of the Ottoman intellectuals and policy-makers by focusing on the work of Ismail Kemal Vlora, Transval Meselesi. Ismail Kemal Bey’s pamphlet on the war is a crucial propagandist instrument and legitimiser of British imperialism in South Africa and in other British colonies. This work aims to grasp the understanding of imperialism and civilisation by the pro-British Ottoman intelligentsia, by looking at their attitude towards the South African War of 1899-1902. In this sense, it aims to make a contribution to Ottoman and South African history.